Pemanfaatan limbah serbuk gergajian kayu merbau (intsia spp.) sebagai briket biomassa untuk energi rumah tangga - Pither Palamba (Prosiding SNTTM, 2025)
This research aims to study the potential of utilizing Merbau sawdust waste as a raw material for biomass briquettes for household energy needs. The methodology applied includes pyrolysis, grinding, and briquette molding, followed by proximate analysis, calorific value analysis, burning test, and thermokinetic analysis using the Arrhenius equation. The study results show that Merbau briquettes have a moisture content of 3.94%, ash 1.98%, volatile matter 34.33%, fixed carbon 59.70%, and a calorific value of 6,567 kcal/kg. The burning test indicates the briquette's capability to heat 3,8 liters of water to boil with a maximum combustion temperature reaching 918 °C. Based on the measured characteristics, briquettes from Merbau sawdust exhibit adequate quality, equivalent to low-calorific coal, and have the potential as an environmentally friendly alternative energy source for the household sector.